The Intervening Role of Customer Satisfaction on the Relationship between Brand Prestige and Behavioral Intentions - Lacap, Jean Paolo G.; Balatbat, Sairen Khay; Malonzo, Joelle Mhyeca Marie C.; Alfaro, Marielle S.; Mungcal, Harold R. (Jurnal The Messenger, 2023)
Introduction: The study investigates the indirect influence of satisfaction on the relationship between brand prestige and behavioral intentions. Methods: A total of 407 respondents participated in the study and they were customers of the leading café in the Philippines. Predictive-causal research design and structural equation modelling via partial least squares (PLS) were employed to measure the direct and indirect hypothesized relationships of the present study. Findings: The results revealed that brand prestige and customer satisfaction significantly and positively influence behavioral intentions. Furthermore, brand prestige was found to be significantly and directly related to customer satisfaction. The mediation analysis indicated that customer satisfaction indirectly affects the link between brand prestige and behavioral intentions. The intervening effect of customer satisfaction on the relationship between brand prestige and behavioral intentions proves that satisfaction is still a vital factor when it comes to favorable outcomes. The significant and positive influence of brand prestige on behavioral intentions is mediated by satisfaction of coffee shop or café customers. Therefore, when customers are satisfied, behavioral intentions among clientele, in particular, in the context coffee shops or café are reinforced. Originality: This study provides novel insights into how customer satisfaction mediates the relationship between brand prestige and behavioral intentions, offering valuable implications for enhancing customer-centric branding strategies in the café industry.